Uso del teléfono inteligente y ansiedad en estudiantes de bachillerato de la Unidad Educativa Puyango - Villamar Erique, Alexander Gabriel (2023)
The arrival of new technologies, such as the smartphone, brings with new ways of life, marked by ease of communication, entertainment and education; due to the time that people dedicate to its use, health problems have increased. The purpose of this study was to determine the use of the smartphone, identify the level of anxiety according to sex and age group, and establish the relationship between both variables among high school students of the Puyango Educational Unit. It was a descriptive study with a quantitative approach, cross-section, made up of 148 students, to whom the Questionnaires Scale of problematic use of mobile phones and Beck's Anxiety Inventory were applied 54.05% (n=80) of participants were represented by women and 45.95% (n=68) by men, regarding age, the group of 15-19 years predominated with 91.89% compared to the group of 11-14 years. It was obtained that 50.68% (n=75) of the adolescents presented habitual use and 22.30% (n=33) problematic use of the mobile phone; the predominant group were women from 15 to 19 years of age with habitual use of 29.05% (n=43). Regarding the level of anxiety, 31.76% (n=47) did not present anxiety, while 68.24% (n=101) had some level of anxiety, with mild and severe levels prevailing, which coincided with 22.97% (n=34). There was a statistically significant relationship with a value of p= 0.000, concluding that the use of the smartphone influences the level of anxiety